2015
DOI: 10.1002/adsc.201401173
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth(III) Bromide‐Catalysed Substitution of Benzyl Alcohols with Arylsulfonylmethyl Isocyanides: An Unexpected Access to Sulfinates

Abstract: Ab ismuth(III)b romide-catalysedd irect substitution of benzyla lcohols with arylsulfonylmethyl isocyanides affords sulfinates under mild acidic conditions.A nu nforeseen reversed reactivity was observed in this highly selectivef ormationo f sulfinates instead of the formation of the usually favoured sulfones. Cytotoxicity tests (in vitro)i ndicated that the sulfinates exhibit antibiotic activity against ah uman leukaemia cell line HL-60, which would widen the structural diversity of this antitumour target and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 78 publications
3
16
0
Order By: Relevance
“…In contrast to Sreedhar' and Xiong's synthetic procedures,, our sulfinate synthesis were carried out under milder conditions (TMSCl, 25 °C or 0 °C), which tolerated more sulfinates and thus expanded the substrate scope of substrates (Scheme a–d). Treatment of L‐menthol ( 7x ) with sodium arenesulfinate 2a under the reaction conditions of our sulfinate synthesis afforded sulfinate 8am in 85 % yield in a 1:1 diastereomeric ratio (Scheme e), similar to the result reported by Oliveira,[7f] indicating that the in situ generation of a carbocation intermediate (Scheme c) from alcohol 7l maybe not a major pathway for this reaction. In order to get more information, reaction of 18 O‐labelled benzyl alcohol ( 7y ) and sodium p ‐toluenesulfinate ( 2a ) was performed in the presence of TMSCl in CH 2 Cl 2 at room temperature (25 °C), which afforded sulfinate 8an in 90 % yield within 1 h (Scheme f).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…In contrast to Sreedhar' and Xiong's synthetic procedures,, our sulfinate synthesis were carried out under milder conditions (TMSCl, 25 °C or 0 °C), which tolerated more sulfinates and thus expanded the substrate scope of substrates (Scheme a–d). Treatment of L‐menthol ( 7x ) with sodium arenesulfinate 2a under the reaction conditions of our sulfinate synthesis afforded sulfinate 8am in 85 % yield in a 1:1 diastereomeric ratio (Scheme e), similar to the result reported by Oliveira,[7f] indicating that the in situ generation of a carbocation intermediate (Scheme c) from alcohol 7l maybe not a major pathway for this reaction. In order to get more information, reaction of 18 O‐labelled benzyl alcohol ( 7y ) and sodium p ‐toluenesulfinate ( 2a ) was performed in the presence of TMSCl in CH 2 Cl 2 at room temperature (25 °C), which afforded sulfinate 8an in 90 % yield within 1 h (Scheme f).…”
Section: Resultssupporting
confidence: 87%
“…However, the concept that one oxygen atom of an arenesulfinate anion 4 acting as the nucleophilic attacking atom is often used consciously or unconsciously to explain the formation of sulfinates 8 (Scheme c), in which the arenesulfinate anion 4 was generated in situ from various reagents ,. [7c], [7e], [7i], Our work necessitates revision of these previous proposed reaction mechanisms in literatures.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Sulfinate esters are versatile sulfinylating source for the construction of various organosulfur compounds including sulfoxides, sulfinamides and sulfones Umpolung character of sulfinate makes them more attractive species for many coupling reactions , . In the recent past, a sulfinate ester probe was reported by Chakrapani's group for thiol bioimaging, whereas Wu et al reported that certain sulfinates exhibit antibiotic activity against a human leukemia cell line HL‐60 . Sulfinates are mainly synthesized by substitution reactions with alcohols .…”
Section: Figurementioning
confidence: 99%
“…All the compounds were characterized using spectral analysis and evaluated for antibiotic activity against a human leukaemia cell line HL-60. [55] Neochoritis and co-workers reported the isocyanide-based MCRs (IMCRs) to afford a-aminoamides as illustrated in Scheme 75. Reaction was optimized by performing a model reaction involving p-methyl-benzaldehyde 149, p-methylaniline 150, carboxylic acid derivatives 151 with tosylmethyl isocyanide using methanol as reaction medium at ambient temperature.…”
mentioning
confidence: 99%